Issues of physical development among the Mongolian youth - Bat-Ochir , Magsar; Munkhnasan, Baljid; Battuvshin, Gurbazar (The New Research of Tuva, 2024)
At the beginning of the research, we proposed the goal of studying the modern trends in physical education at the Mongolian University of Science and Technology through analysis and comparative assessments. As a result of the study, it was observed that comprehensive education in England, sports education using technical and technological advances in Australia, sports teaching for happiness in Japan and China and skills education and physical education in Mongolia are the dominant teaching approaches. In the course of the analysis, it has been found out that there is a lack of attitude towards physical education in Mongolia, and we have determined the extent to which it has been effective through a test study.One of the main goals of our work is to study the issue of physical development of the Mongolian youth in years past.The article presents the results of the unprecedented physical development test of the first-year students enrolled in the Mongolian University of Science and Technology from 2008 to 2018. We used the “Test to Determine the Level of Physical Development and Fitness of the Population”. Actually, this test named after the President of Mongolia Mr. Tsakhiagiin Elbegdorj has been implemented at the national level.During the test, height, weight, speed, strength, flexibility and endurance of students were studied by the movement test method. The test was evaluated according to the approved methodologyю. And as a result, we used quantitative and statistical research methods, performed reliability and statistical tests for each questionnaire and data obtained and analyzed the correlation of factors. If we look at physical development levels of all students, there were 14 percent with poor results and 44 percent with insufficient ones. The physical development of the majority of participants (58 percent) was rated below the sufficient level (17 points) that a person of that age should have. In terms of gender, 53 percent of male students and 65 percent of female students had insufficient physical development.According to the data of a sociological questionnaire survey of students participating in the test, 58.1 percent did not exercise or play sports. It was an interesting observation that coincided with the result that 58.0 percent of the test participants had insufficient physical development. According to our research, the majority of Mongolian students and young people had a low level of physical fitness, and one of every six students had weight problems. This may indicate that the approach to teaching skills development and physical education is somewhat ineffective.The theoretical and practical significance of the research is that the current situation regarding physical development of students and youth can be determined and the results can serve as a basis for making detailed policies and decisions for the development of physical activity and sports among young people.Today, students and youth are the most important segment of the population that drives the economy and human development of Mongolia, so it is important to cultivate a healthy and physically fit nation relying on the fact that physical activity and sports should be available for all people.
Keywords: student; physical education; sports; sports management; Mongolia